2011
DOI: 10.2320/matertrans.l-mz201103
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cycle Fatigue of Ultrafine-Grained Aluminum at Low Temperatures

Abstract: Ultrafine-grained (UFG) Al of 99:98$99:99% purity was fabricated by equal channel angular pressing. Fully reversed tensioncompression low-cycle fatigue tests were carried out under plastic strain control at various temperatures between 83 K and 300 K. At 300 K, UFG Al showed rapid cyclic softening. As test temperature decreased, cyclic softening became less significant and at 83 K, UFG Al showed cyclic hardening till saturation. Formation of shear bands and development of dislocation structure were the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(2) Evidently, thermally activated processes occur during thermal cycling and are more significant at higher temperatures [14], [36], [37]. The occurrence of thermally activated phenomena such as recrystallization during thermomechanical fatigue is not in itself a controversial notion and has been widely reported even for isothermal fatigue conditions [14], [46], [47]. However, its influence on failure is yet to be captured meaningfully by existing PoF models for wire bonds.…”
Section: Some Phenomenological Considerations For Wire Bond Lifetime ...mentioning
confidence: 99%
“…(2) Evidently, thermally activated processes occur during thermal cycling and are more significant at higher temperatures [14], [36], [37]. The occurrence of thermally activated phenomena such as recrystallization during thermomechanical fatigue is not in itself a controversial notion and has been widely reported even for isothermal fatigue conditions [14], [46], [47]. However, its influence on failure is yet to be captured meaningfully by existing PoF models for wire bonds.…”
Section: Some Phenomenological Considerations For Wire Bond Lifetime ...mentioning
confidence: 99%
“…Therefore, the calculated values of ¡ listed in Table 1 are close to the theoretical value. Figure 6 summarizes the experimental results of the inverse channel width under a given stress amplitude for single-crystalline Al, 32,37,53) UFG Al, 39) CG Al and UFG Al in this study. From the slope of the straight line, we find ¡ = 2.1 which is again in good agreement with the theoretically-estimated value.…”
Section: )mentioning
confidence: 99%
“…We have recently reported that test temperature plays an important role on the fatigue behavior of high purity UFG Al and very fine dislocation wall structure is formed when tested at 83 K in grains smaller than a few micrometers. 38,39) In this study, low-cycle fatigue tests were carried out under plastic-strain control at 77 K using CG and UFG Al, and monotonic tensile tests were performed in succession either at 300 or 77 K after the fatigue tests. From the results of monotonic tensile tests and transmission electron microscopy (TEM), the formation and stability of the fatigued dislocation structure are studied.…”
Section: )mentioning
confidence: 99%